A single test approach for accurate and sensitive detection and taxonomic characterization of Trypanosomes by comprehensive analysis of internal transcribed spacer 1 amplicons - Gaithuma, Alex Kiarie; Yamagishi, Junya; Martinelli, Axel; Hayashida, Kyoko; Kawai, Naoko; Marsela, Megasari; Sugimoto, Chihiro (PLOS Neglected Tropical Diseases, 2019)
Author summary Tsetse flies are central actors in the transmission of Trypanosomes to vertebrate hosts. Therefore, detection of Trypanosomes in the tsetse flies is important for understanding the epidemiology of African trypanosomiasis as a component of new control or surveillance strategies. We have developed a method that combines multiplex PCR and next-generation sequencing for the detection of different Trypanosome species and subspecies. Similar to the widely used bacterial metagenomic analysis protocol, this method uses a modular, two-step PCR process followed by sequencing of all amplicons in a single run, making sequencing of amplicons more efficient and cost-effective when dealing with large sample sizes. As part of this approach, we designed novel Internal Transcribed Spacer 1 primers optimized for short read sequencing and have slightly better sensitivity than conventional primers. Taxonomic identification of amplicons is based on BLAST searches against the constantly updated NCBI’s nt database. Our approach is more accurate than traditional gel-based analyses which are prone to misidentification of species. It is also able to discriminate between subspecies of T. congolense, T. simiae, T. vivax, and T. godfreyi species. This method has the potential to provide new insights into the epidemiology of different Trypanosome genotypes and the discovery of new ones.